2016
DOI: 10.1597/14-191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Palatoplasties on the Facial Morphology of Early Mix Dentition Stage Children with Unilateral Cleft Lip and Palate

Abstract: Early two-stage Furlow palatoplasty leads to more protruded upper lip, providing more anteriorly positioned upper incisors compared with PB, at least at the early mixed dentition stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
(26 reference statements)
0
11
0
2
Order By: Relevance
“…[27] Notwithstanding, the literature lacks consensus on the type of primary plastic surgery, suitable technique, and surgical time that would cause the most restrictive effects in these individuals. [69]…”
Section: Introductionmentioning
confidence: 99%
“…[27] Notwithstanding, the literature lacks consensus on the type of primary plastic surgery, suitable technique, and surgical time that would cause the most restrictive effects in these individuals. [69]…”
Section: Introductionmentioning
confidence: 99%
“…This protocol comprises soft palate plasty at 1 year of age using a modification of the double-opposing Z-plasty (Furlow, 1986), followed by hard palate closure at 1.5 years of age. Although the interval between soft palate plasty and hard palate closure is short, a number of clinical studies—including research by our department—have reported more favorable palatal growth with this protocol (Kitagawa et al, 2004; Yamanishi et al, 2009; Nishio et al, 2010) than with conventional 1-stage pushback palatoplasty (Wardill, 1937), although several researchers reported conflicting results (Tome et al, 2016). Positive palatal development following this protocol is due to several factors, including an innate decrease in cleft width of the hard palate after soft palate plasty (Nishio et al, 2001), which reduces surgical interference at hard palate closure, resulting in an improved palatal development (Kitagawa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A distância intertuberosidades (TT') não apresentou modificações significativas durante o período estudado, o comprimento total do arco dentário (I-TT') não apresentou modificações significantes entre T1 e T2, mas apresentou crescimento entre T1 e T3. Outros estudos corroboram os resultados encontrados neste estudo, validando a suposição de que a queiloplastia não interfere no crescimento intertuberosidades (MAZAHERI, HARDING, NANDA, 2012;BRAUMANN et al, 2002;HUANG et al, 2002;REISER, SKOOG, ANDLIN-SOBOCKI, 2013;JORGE et al, 2016 (ROSS, 1987;HUANG et al, 2002), girando os segmentos em direção à linha média e diminuindo a amplitude da fissura (WADA et al, 1984) (CARRARA et al, 2016;TOME et al, 2016).…”
Section: Variáveisunclassified
“…Estes procedimentos representam uma abordagem importante do protocolo reabilitador (SHI e LOSEE, 2015), pois procuram reconstituir o defeito anatômico resultando em reparo funcional e estético, além de possibilitar condições favoráveis para uma qualidade de vida satisfatória (FREITAS et al, 2012;JONES et al, 2016), com o mínimo de perturbação no potencial de crescimento dos arcos dentários (MORIOKA et al, 2018 (MIKOYA et al, 2015;TOME et al, 2016, REDDY et al, 2017.…”
Section: Introdução E Síntese Bibliográfica Introdução E Síntese Biblunclassified